PRESOLAR DIAMOND, SILICON CARBIDE, AND GRAPHITE IN CARBONACEOUS CHONDRITES: IMPLICATIONS FOR THERMAL PROCESSING IN THE SOLAR NEBULA - Huss G.R.; Meshik A.P.; Smith J.B.; Hohenberg C.M. (My University, 2003)
We have determined abundances of presolar diamond, silicon carbide, graphite, and Xe-P1 (Q-Xe) in eight carbonaceous chondrites by measuring the abundances of noble gas tracers in acid residues. The meteorites studied were Murchison (CM2), Murray (CM2), Renazzo (CR2), ALHA77307 (CO3.0), Colony (CO3.0), Mokoia (CV3ox), Axtell (CV3ox), and Acfer 214 (CH). These data and data obtained previously by provide the first reasonably comprehensive database of presolar-grain abundances in carbonaceous chondrites. Evidence is presented for a currently unrecognized Ne-E(H) carrier in CI and CM2 chondrites.After accounting for parent-body metamorphism, abundances and characteristics of presolar components still show large variations across the classes of carbonaceous chondrites. These variations correlate with the bulk compositions of the host meteorites and imply that the same thermal processing that was responsible for generating the compositional differences between the various chondrite groups also modified the initial presolar-grain assemblages. The CI chondrites and CM2 matrix have the least fractionated bulk compositions relative to the sun and the highest abundances of most types of presolar material, particularly the most fragile types, and thus are probably most representative of the material inherited from the sun's parent molecular cloud. The other classes can be understood as the products of various degrees of heating of bulk molecular cloud material in the solar nebula, removing the volatile elements and destroying the most fragile presolar components, followed by chondrule formation, metal-silicate fractionation in some cases, further nebula processing in some cases, accretion, and parent body processing. If the bulk compositions and the characteristics of the presolar-grain assemblages in various chondrite classes reflect the same processes, as seems likely, then differential condensation from a nebula of solar composition is ruled out as the mechanism for producing the chondrite classes. Presolar grains would have been destroyed if the nebula had been completely vaporized. Our analysis shows that carbonaceous chondrites reflect all stages of nebular processing and thus are no more closely related to one another than they are to ordinary and enstatite chondrites.